2016
DOI: 10.1002/ange.201509477
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR and DFT Analysis Reveal Structural and Electronic Transition State Features for RhoA‐Catalyzed GTP Hydrolysis

Abstract: Molecular details for RhoA/GAP catalysis of the hydrolysis of GTP to GDP are poorly understood. We use 19 FNMR chemical shifts in the MgF 3 À transition state analogue (TSA) complex as aspectroscopic reporter to indicate electron distribution for the g-PO 3À oxygens in the corresponding TS, implying that oxygen coordinated to Mg has the greatest electron density.This was validated by QM calculations giving apicture of the electronic properties of the transition state (TS) for nucleophilic attack of water on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…[26a] More recent work has sought to establish the extent to which MgF3 -resembles PTx in the TS for GTP hydrolysis catalyzed by the RhoA/RhoGAP complex. [20] Specifically, this study, which employed DFT calculations on a very large active site model, containing 91 heavy atoms, demonstrated that the observed 19 F chemical shifts for the RhoA·RhoGAP·GDP·MgF3 -complex can indeed be interpreted as indirect measures of the relative electron densities of the cognate oxygen atoms in the "true" TS for attack of water on the terminal phosphate of GTP. [20] 6.4 AlF3 complexes.…”
Section: Mgf3 Complexesmentioning
confidence: 86%
See 4 more Smart Citations
“…[26a] More recent work has sought to establish the extent to which MgF3 -resembles PTx in the TS for GTP hydrolysis catalyzed by the RhoA/RhoGAP complex. [20] Specifically, this study, which employed DFT calculations on a very large active site model, containing 91 heavy atoms, demonstrated that the observed 19 F chemical shifts for the RhoA·RhoGAP·GDP·MgF3 -complex can indeed be interpreted as indirect measures of the relative electron densities of the cognate oxygen atoms in the "true" TS for attack of water on the terminal phosphate of GTP. [20] 6.4 AlF3 complexes.…”
Section: Mgf3 Complexesmentioning
confidence: 86%
“…[43] More recently, computational methods have also validated the idea that tbp MFx structures are analogs of the phosphoryl group in the "true" transition states for enzyme-catalyzed reactions, and provide useful information on the extent to which MFx moieties resemble ground states or TSs in enzyme-catalyzed PTx. [20] Although the covalent character of P-O and M-F bonds is very different in the GS and (most likely) the TS, these calculations demonstrate that differences in NMR 19 F chemical shifts do provide insights into the environments experienced by the oxygen atoms in the "true" TS for the reaction.…”
Section: Computational Analyses Of Mf X Complexesmentioning
confidence: 91%
See 3 more Smart Citations